Faktor-Faktor yang Berhubungan dengan Kunjungan Antenatal Care Ibu Hamil di Puskesmas - Gustika Anggriani (STIKES Citra Delima Bangka Belitung, 2020)
Increase in maternal KPS in Indonesia which carried out antenatal care from 95.2% to 96.1%, the ideal proportion of k1 from 81.3% to 86%, the proportion of antenatal care (k4) from 70% to 74.1% while the proportion of deliveries in health facilities from 66.7% to 79.3% (Riskesdas 2013). The purpose of this study was to determine the ANC visit to prabumulih city market health centers in 2019. This study used an Analytical Survey using the Cross Sectional approach. The population of this research is 54 pregnant women with trimester III gestational age. The sample is 54 respondents. In the univariate analysis it was found that respondents who were at risk were 33 respondents (61.1%) and respondents who were not at risk were 21 respondents (38.9%). High risk parity was 35 respondents (64.8%) and low risk parity was 19 respondents (35.2%). Highly educated as many as 41 respondents (75.9%) and low as many as 13 respondents (24.1%). Good knowledge as many as 43 respondents (79.6%) and less well as many as 11 respondents (20.4%). Bivariate analysis shows that maternal age has a significant relationship with antenatal care visits (p value 0.002), maternal parity has a significant relationship with antenatal care visits (p value 0,000), maternal education has a significant relationship with antenatal care visits (p value 0,000) and Knowledge Mother has a significant relationship with antenatal care visits (p value 0,000). The conclusion of this study is that there are factors that are associated with antenatal car.